Manfaat Relaksasi Otot Progresif Bagi Klien DM Tipe II Untuk Mengurangi Gejala Fatigue - Reny Sulistyowati (Jurnal Surya Medika (JSM), 2021)
Fatigue is a widespread clinical complaint among adults with type 2 diabetes. Fluctuating glucose levels can cause fatigue. Several factors are associated with fatigue in diabetic patients, including physiological factors such as hypoglycemia or hyperglycemia, psychological factors such as depression associated with diabetes. Progressive muscle relaxation is a procedure to get relaxation in the muscles through two steps, namely by applying tension to a muscle group and stopping the tension then focusing on how the muscle relaxes, feeling the sensation of relaxation and fatigue is reduced. The aim of this study was to identify the effect of progressive muscle relaxation on fatigue symptoms in type II DM clients in 15 control groups and 15 intervention groups. The research method used a quasi-experimental design with a pretest-posttest control group design approach, consisting of one treatment (in the intervention group) and a control group. Data analysis was performed using univariate and bivariate analysis using t-independent and t-dependent tests. Wilcoxon test results in the intervention group and the control group showed a significant p-value of 0.002 (<0.05), meaning that there was a significant difference in fatigue symptoms in the intervention group before and after the intervention. This shows that there was a decrease in fatigue symptoms in the intervention group before and after combination OHO therapy and progressive muscle relaxation exercises (previously the average respondent in the intervention group experienced symptoms of severe fatigue, after intervention, the average value of fatigue symptoms turned into mild fatigue ). Conclusion: Progressive muscle relaxation combined with OHO therapy can reduce symptoms of fatigue compared to only OHO therapy.